A Cameroon Western Regions high-fat diet (MACAPOS 2) induces visceral obesity in rat - Sandrine Nkoubat Tchoundjwen; Armel Georges Kamgang Tchawou; Clémence Mvongo; Adamou Mfopa; Joseph Ngakou Mukam; Paul Aimé Noubissi; Gaetan Olivier Fankem; René Kamgang; Jean Louis Essame Oyono (Heliyon)
The prevalence of obesity increases yearly in the world. The traditional local diet of the Western Regions of Cameroon was suspected to be the main contributor to the high prevalence of obesity in these Regions. This study aimed to evaluate the effects of a Cameroon-comparable fat diet on visceral obesity in rats.Two groups of male Wistar rats were fed for four months with respectively a normal diet (ND) (3400 kcal/kg of food) and a high-fat diet (HFD) containing maize, cassava, palm oil, and sugar (MACAPOS 2): 35 % carbohydrate, 55 % fat and 10 % proteins (4730 kcal/kg of food). Lee index, body weight, food intake, blood and hepatic lipids, body fat, insulin resistance, glucose tolerance, glycemia, serum insulin, leptin, and adiponectin were evaluated.HFD significantly (P < 0.01) increased body weight and decreased food intake. After four months of diet, 88.8 % of HFD rats were obese (Lee index >30 g/cm), and HFD significantly increased visceral and subcutaneous fats compared to ND. HFD increased triglyceride, total cholesterol, Low-density lipoprotein-cholesterol levels, and the atherogenic index, while the high-density lipoprotein-cholesterol level was decreased. The hepatic triglyceride and total cholesterol levels significantly (P < 0.01) increased in HFD, compared to ND. In HFD, the fasting blood glucose, serum insulin, and leptin levels significantly (P < 0.01) increased, meanwhile adiponectin decreased. HFD-induced glucose intolerance and insulin resistance in rats.Based on our findings, we can conclude that HFD MACAPOS 2 can induce central obesity. Therefore, it can be used as a model of diet-induced obesity.